Efecto de la Hipodoncia en relación a su origen congénito. revisión bibliográfica - Jonnathan Bryan, Torres Arias (2021)
ABSTRACT This research addressed the effect of hypodontia concerning its congenital origin because it is the most common developmental anomaly in humans and constitutes a clinically challenging problem for the dentist at the time of consultation with the patient. The main objective of the research was to describe the effects caused by hypodontia. Its congenital origin through a review of the literature, identifying the etiology, possible causes, and finally specifying the types of treatments used to treat this dental anomaly. The development of this study was carried out through the analysis of various scientific articles, books, and magazines based on scientificacademic evidence. It concluded that the effects caused by hypodontia concerning its genetic origin are influenced by the severity of the same, which means that the greater the lack of teeth, the more people can present morpho-craniofacial and dental alterations. It can affect both the esthetic and the functional part: chewing, imbalance in the chewing, chewing and dental function, and practical: (mastication, vocal and occlusal imbalance, muscle contractures and dysfunctions temporomandibular joint). It results in complex socio-psychological problems and generates an adverse impact on the quality of life of people who suffer from it. Key words: Hypodontia, congenital, dental anomalies. Reviewed by: Ms.C. Ana Maldonado León ENGLISH PROFESSOR C.I.0601975980